EMPLOYEE EVALUATION INFORMATION SYSTEM PT. DHL EXPRESS INDONESIA WITH TIMESHEET PARAMETERS / ONLINE ABSENCE WITH OPENID AND OAUTH2 SECURITY - Wisnu Sukma Maulana (Asosiasi Dosen Muda Indonesia, 2022)
PT DHL Express Indonesia (DHL) is a courier and freight forwarding service company between regions in Indonesia. Bearing in mind the vast territory in Indonesia, DHL records 314 thousand shipments per year or 860 shipments per visit. In order to improve the shipping service, DHL took the initiative to request a system that could support the timesheet or the attendance of its couriers properly and safely. Making an absent or online attendance system using two security technologies namely OpenID and Oauth2. Both of these security technologies guarantee timesheet data leakage or absenteeism from the client side ie the couriers by the server side namely the central DHL.